Penerapan Bagi Hasil Maro Perspektif Akad Mukhabarah (Sharia Faculty Islamic Economic Law Study Department, 2020)
Mukhabarah is a profit sharing partnership between the land owner and the sharecropper, where the land owner surrenders his land to the sharecropper and the capital is fully borned by the sharecropper. Mukhabarah which are take a place in Brakas Village, people are more familiar with